From Big Ag to Campus Cafeterias: Intersections of Food-Supply Networks as Technical Communication Pedagogy. Issue 2 (23rd November 2018) - Richards, Jessie Lynn; Lenart, Joshua; Sumner, David; Christensen, Douglas
This article presents a pedagogical approach to teaching technical and professional writing with an eye toward cultivating awareness and generating informed research among undergraduate students about food production and its various, intricate networks between Big Ag and campus cafeterias. Our pedagogy, influenced by interdisciplinary content, is designed to teach students to differentiate between food processes—such as production versus distribution and consumption—by viewing these networks as communicative practices rather than as inevitable chains or simple functions of one another. Our approach encourages students to locate and analyze differences between interdependent, but seemingly disparate pathways and to make visible communicative intersections that are often rendered invisible and inevitable when not given conscious attention. We base our approach on best teaching practices in technical communication and current literature about food sourcing, sustainability, and ethical food production practices. By focusing on food pathways as a means of teaching technical communications, we are helping students become more adept writers while also educating them about the processes that contribute to what they put into their bodies and how those choices resonate throughout the public sphere. A chief contribution of this article is a description of how students populate a Food Pathways Matrix, which informs their writing and research as they revisit it throughout the semester.